Application of Magnus series for polarization evolution in fibers - N.Korneev. (Revista Mexicana de Física, 2002)
We apply the technique of Magnus series to build approximations for polarization evolution in fibers with varying twist and birefringence. Conditions for trajectory mixing on Poincaré sphere are identified. The technique relates realistic perturbation parameters to the parameters of popular coarse step method of numerical simulation. We demonstrate that liner polarization mode dispersion, if it is a dominant process, leads for big propagation lengths to a speckle-like output pulse shape.